2015
DOI: 10.1038/ncomms7959
|View full text |Cite
|
Sign up to set email alerts
|

Induction and control of supramolecular chirality by light in self-assembled helical nanostructures

Abstract: Evolution of supramolecular chirality from self-assembly of achiral compounds and control over its handedness is closely related to the evolution of life and development of supramolecular materials with desired handedness. Here we report a system where the entire process of induction, control and locking of supramolecular chirality can be manipulated by light. Combination of triphenylamine and diacetylene moieties in the molecular structure allows photoinduced self-assembly of the molecule into helical aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
122
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(127 citation statements)
references
References 62 publications
5
122
0
Order By: Relevance
“…[24,25] In addition, Seu and Kim have demonstrated that opposite helicals enses in photooxidizedt riphenylamine stacks can be induced by applying circularly polarized light of opposite handedness,o pening an ew route towards the formation of supramolecular chiral conductors. [26] However,supramolecular interactions do not always result in the formationo ft hermodynamically stables tates. Pathway complexity-thedifferentreaction pathways and intermediates that can occur in as elf-assembling system-has recently been disclosed in severals ystems and the importance of controlling complex kinetic processes is af undamental next step to take.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] In addition, Seu and Kim have demonstrated that opposite helicals enses in photooxidizedt riphenylamine stacks can be induced by applying circularly polarized light of opposite handedness,o pening an ew route towards the formation of supramolecular chiral conductors. [26] However,supramolecular interactions do not always result in the formationo ft hermodynamically stables tates. Pathway complexity-thedifferentreaction pathways and intermediates that can occur in as elf-assembling system-has recently been disclosed in severals ystems and the importance of controlling complex kinetic processes is af undamental next step to take.…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy is a polymeric method, in which rigid main-chain or chiral units appear as helical structures with exclusive handedness [18][19][20] . The local chiral signals of monomeric molecules are primarily transformed to conformational chiral information during chirality transfer 15,21,22 , and this information could be switchable instead of being permanent [23][24][25] , although preserving uniformity for local and global chirality is desirable for better understanding chiral amplification and recognition. Moreover, significant effort has been put into achieving visible observation of chiral recognition and discrimination on the macroscopic scale.…”
mentioning
confidence: 99%
“…However,i nt he presence of divalent metal ions, chirality of these helical fibers was enhanced throughm etal coordination and could be transformed into nanospheresw ith an excess amount of the ions. [7] Amongc hiral monomers, C 3 -symmetrical molecules based on benzene-1,3,5-tricarboxamides (BTAs) represent au nique kindo fs upramolecular building blocks, which can self-assemble in ac ooperative fashion into helical, one-dimensionals tacks through threefold hydrogen bonding.P ioneering work on BTAs showst hat well-defined fibers can be formed through both "majority-rules" and "sergeants-and-soldiers principle", [8] and the supramolecular handednessc an be controlled by stereogenic centers in the pendants, [9] amphiphilicity, [10] light [11] and solvents. [1] Metal-ion coordination has been provent ob eapowerful tooli nr egulating protein assembly.…”
mentioning
confidence: 99%
“…[3] Supramolecular helicalp olymers can be formed throughc oordination of pyridine units with transition-metal ions. [7] Amongc hiral monomers, C 3 -symmetrical molecules based on benzene-1,3,5-tricarboxamides (BTAs) represent au nique kindo fs upramolecular building blocks, which can self-assemble in ac ooperative fashion into helical, one-dimensionals tacks through threefold hydrogen bonding.P ioneering work on BTAs showst hat well-defined fibers can be formed through both "majority-rules" and "sergeants-and-soldiers principle", [8] and the supramolecular handednessc an be controlled by stereogenic centers in the pendants, [9] amphiphilicity, [10] light [11] and solvents. [5] Overall,m etal-ionm ediated supramolecular assembly is dominated by balance between coordination, p-p stacking, van der Waals interactions, and efficiencyo fs upra-molecular polymerization;t he helical sense and supramolecular chirality are determined by coordination constants, steric hindrance, molecular packing modes and counter-anions.…”
mentioning
confidence: 99%
See 1 more Smart Citation